Evaluation Of Morbid Obese Patients In Terms Of Sexual Dysfunctions: A Cross-Sectional Study - Lezzan Keskin; İbrahim Şahin; Lale Gönenir Erbay; Bahri Evren; Bülent Yaprak (Acta Medica Alanya)
Aim: Obesity is a risk factor for sexual dysfunction. The aim of this study was to determine the frequency of sexual dysfunction in patients diagnosed with morbid obesity.Methods: The patient group included in the study consisted of 78 morbidly obese patients with BMI≥40 kg/m2 and 68 healthy individuals with normal BMI. The data were obtained by using the sociodemographic information form filled by the participants, Beck anxiety scale, Beck depression scale and Golombok Rust Sexual Satisfaction Inventory.Results: Obese individuals were found to have sexual dysfunction compared to individuals with normal body BMI (p<0.05). When the Golombok Rust subscale scores of obese men were compared to those of normal-weight individuals, a significant deterioration was found in all subscale scores, including frequency, communication, satisfaction, avoidance, touch, impotence and premature ejaculation. In addition, the anxiety and depression scores of obese individuals were shown to be higher than those of normal-weight individuals (p<0.05).Conclusion: Morbidly obese individuals should be evaluated in terms of sexual functions. We believe that regulating obesity treatment, including possible treatment for sexual dysfunction, will increase the success rate and enhance the quality of life for patients.